Identidades raciais negras nos materiais didáticos de língua espanhola: um olhar decolonial - Rodrigues, Daiane Santos (2023)
Despite living in a diverse country, we still observe conflicts arising from the lack of acceptance of diversity, whether it be related to gender, ethnic-racial background, or class, among other factors. We are aware that social groups advocating for equal rights are gaining significant prominence and bringing about substantial changes. However, even with all these achievements, we still encounter stereotypes and prejudiced attitudes. With the aim of addressing this issue and raising awareness among students about the role of diversity in schools, this research aims to examine whether the Spanish language textbooks approved by the last National Textbook Program (PNLD) in 2018 include an approach concerning the (re)construction and valorization of social racial identities. Operating on the assumption that these issues need to be integrated into the school curriculum, it is essential for teachers and students to consider Spanish language classes as a platform for discussions on these topics. This is crucial for them to recognize the diversity in their social environment, as well as the need to advocate for equal rights. It is noteworthy that language teachers should be able to supplement instructional materials and develop a pedagogical proposal that embraces identity valorization and is closely aligned with the students' reality. To this end, the methodology employed is qualitative and interpretative in nature. Consequently, this work is grounded in the theoretical perspectives of Ferreira (2012), Freitas (2012), Hall (2006), Matos (2014, 2018), Moita Lopes (2003), Quijano (2005), Silva Júnior and Matos (2019), Walsh (2009), among others. It is of great importance to address diversity, especially in the multicultural country in which we live, by giving a voice to issues that society often marginalizes. This configures foreign language classes with a decolonial perspective so that students can recognize the importance of identity reconstruction and valorization and their societal role. The results obtained indicate that there is no equity between Black and White individuals in the analyzed textbooks, perpetuating Black racial inequality and highlighting the predominance of appearances and literary productions more frequently authored by White individuals.